ADVANTAGES OF THE APPLICATION OF MODERN ELEMENTS OF JUDO PEDAGOGICAL TECHNOLOGY IN THE FORMATION OF VISUALLY IMPAIRED AND VISUALLY IMPAIRED CHILDREN AND ADOLESCENTS - Khasanov Djamshid Halimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article covers the ways of interactive and information use, Organization and its methods in the formation of visually impaired and visually impaired children and adolescents in the lessons of modern judo pedagogical technology.